Analisis Teori dan Referensi Pembelajaran Bilingual: Metode, Strategi, Evaluasi, dan Aspek Lainnya - Ikhtiarini, Shinta Anugrah; Savanamira, Leyla; Rachmawati, Dwi; Widagdo, Arif; Baskara, Bintang; Heriyanto, Firstyansa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Bilingual education is one of the learning strategies developed to answer global challenges in the world of education, especially in forming foreign language competencies of students since elementary school level. In the Indonesian context, the implementation of bilingual education still faces various obstacles, especially related to the lack of integration between theory and practice in learning. This study aims to analyze the theory and references of bilingual learning by reviewing methods, strategies, evaluations, and relevant supporting factors in the context of learning in elementary schools. The study was conducted using a literature review approach to various relevant national and international scientific articles. The results of the study indicate that bilingual learning requires methods that not only deliver material, but also develop students' cognitive functions. Effective learning strategies include a translanguaging approach, local cultural integration, and multimodal use of technology. Evaluation in bilingual learning needs to be designed holistically, assessing students' mastery of content as well as linguistic abilities. Meanwhile, the main supporting factors for the success of bilingual learning include teacher competence, school environmental support, active family roles, and an inclusive learning atmosphere. These findings are expected to contribute to the development of a bilingual learning model that is adaptive to the needs of the 21st century and becomes a practical reference for educators and education policy makers.